2015
DOI: 10.1016/j.jval.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient Registries Supporting Reimbursement Decisions: The Case of Oxaliplatin for Treatment of Stage III Colon Cancer

Abstract: Patient registries may be an efficient way to gather data on new medical treatments, but they need to be carefully designed and evaluated, in particular regarding their follow-up time. For each purpose, data gathering can be tailored to make sure decisions are taken at the moment that sufficient data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Firstly, our results are not the first to describe the antiinflammatory effect of pioglitazone on colitis. Secondly, although it has been reported that intrathecal or systematical of pioglitazone attenuates hyperalgesia in a neuropathic pain model [20,50]. However, we only observe the effects of systematical administration of pioglitazone on colitis and related pain hypersensitivity.…”
Section: Limitationscontrasting
confidence: 54%
“…Firstly, our results are not the first to describe the antiinflammatory effect of pioglitazone on colitis. Secondly, although it has been reported that intrathecal or systematical of pioglitazone attenuates hyperalgesia in a neuropathic pain model [20,50]. However, we only observe the effects of systematical administration of pioglitazone on colitis and related pain hypersensitivity.…”
Section: Limitationscontrasting
confidence: 54%
“…Several examples of difficulties with outcomes-based agreements are available in the literature. A Dutch evaluation of an outcomes-based managed entry agreement of oxaliplatin for treatment of stage III colon cancer that collected additional data through a patient registry found that patient heterogeneity made it problematic to estimate incremental cost-effectiveness of the treatment using the collected data (Mohseninejad et al, 2015 ). A Dutch hematological malignancies registry reported that the three main issues were confounding by indication, missing data, and insufficient comparable patient numbers (Blommestein et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Organising and performing data collection are two of the most frequently discussed barriers for implementation of OBAs for payers, developers and healthcare providers (Sudlow and Counsell, 2003;de Pouvourville, 2006;Carlson et al, 2010;McCabe et al, 2010;Raftery, 2010;Stafinski et al, 2010;Williamson, 2010;Jaroslawski and Toumi, 2011b;Klemp et al, 2011;Neumann et al, 2011;Cascade et al, 2012;Goldenberg and Bachman, 2012;Xoxi et al, 2012;Bibeau et al, 2014;Gibson and Lemmens, 2014;Li et al, 2014;Garattini et al, 2015;Lu et al, 2015;Lucas and Wong, 2015;Mohseninejad et al, 2015;Barlas, 2016b;Carr and Bradshaw, 2016;Malik, 2016;Pouwels et al, 2016;van de Wetering et al, 2017;Duhig et al, 2018;Ernst and Young, 2018a;Ernst and Young, 2018b;EXPH, 2018;Goldenberg et al, 2018;Jorgensen et al, 2018;Stirnadel-Farrant et al, 2018;Urbinati et al, 2018;Federici et al, 2019;Macaulay and Turkstra, 2019;Mundy et al, 2019;Pace et al, 2019;Kannarkat et al, 2020). First, experiences with OBAs in the Netherlands and the United Kingdom highlight that...…”
Section: The Organization Of Data Collectionmentioning
confidence: 99%
“…Therefore, Makady et al recommend to invest in the extensive training of healthcare professionals, manufacturers and payers on analysis and interpretation of the results for OBAs . Furthermore, progress of data collection could be monitored by frequent payer audits to correct for errors during the course of the agreement and to verify if the registry is providing useful information (Mohseninejad et al, 2015;Annemans and Pani, 2017;Gerkens et al, 2017;FoCUS, 2019b).…”
Section: The Organization Of Data Collectionmentioning
confidence: 99%